PERFORMANCE OF MASONIC SOLAR STILL WITH BOX TYPE INTERNAL CONDENSER IN SUMMER CLIMATE - Mahesh D. Joshi; Sandeep R. Kumbhar; Madhav G. Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
Solar Desalination via Solar still is the best method of obtaining 2-3 liter of potable water in a typical summer day from brackish water. Solar still in its state of art is ‘Rain Machine’ or ‘Hydrological Cycle in trapezoidal basin.’ In analysis of solar still, it has been proved and well accepted that, rate of condensation is strong function of temperature difference between inner glass cover (condensing cover) and basin water temperature. In architecture and working of Masonic solar still, it is found that, temperature difference is not conducive for condensation in summer days and at peak Sun shines hours. Literature review and opinion of expertise suggest advent of internal condenser in solar still. Among different configurations box type copper metal make internal condenser is fabricated and fixed at back wall of still. Water is fed to box from overhead tank so as to get natural siphoning and cooling effect inside the still.